Prevalence and Associated Factors of Malnutrition in Under Five Children in a Rural Mountainous Area of Nepal: A Community Based Cross Sectional Study - Chataut, J.; Jonchhe, S. (Kathmandu University Medical Journal, 2020)
Background Nutrition is believed to be very essential for socio economic development of the country and is an essential component of sustainable development goals. Malnutrition is a major public health problem in Nepal and is more common among under-five year children. Malnutrition among children is complex problem globally, affecting the physical, mental and social development. Objective To estimate the prevalence and explore the associated factors of malnutrition in study population. Method It was a community based cross-sectional study conducted among rural population of Nepal. Wards were selected by simple random sampling technique and household in each ward were selected by systemic random sampling. The mothers of 302 participants aged 12 to 59 months were interviewed for requisite information using pretested questionnaire and anthropometric measurements were taken using standard technique for each participant. Statistical Package for Social Sciences (SPSS) version 16.0 was used for data analysis. Result The prevalence of underweight, stunting and wasting was 36.8%, 37.5%, and 14.6% respectively. We found statistical significant association between underweight and children in lower age group, larger family size, lower level of mother’s education and illness in past one month. Factors that are significantly associated with stunting are children in lower age group, lower level of mother’s education and illness in past one month and wasting is significantly associated with children in lower age group. Conclusion This study showed the prevalence of malnutrition is high in study population. Factors associated with malnutrition were child’s age, family size, mother’s education and illness in past one month.